Enhanced Expression of Two ISGs as Potential Biomarkers of Prognosis in HIV-Infected Immunological Non-Responders - Xin Zhang; Lin He; Ruifeng Zhang; Haolan Sun; Liguo Zhang; Cong Jin (Zoonoses)
No novel biomarkers are currently available for evaluating immune reconstitution among people living with HIV/AIDS (PLWH) receiving combined antiretroviral treatment (cART). The objective of this study was to analyze the expression patterns of interferon-stimulating genes (ISGs) in PLWH with the aim of identifying potential biomarkers for immune reconstitution. Study samples were collected from 105 PLWH, including 47 immunological non-responders (INRs) and 58 immunological responders (IRs). The expression of eight ISGs in the peripheral blood in INRs and IRs were detected by RT-qPCR. Expression differences between groups were analyzed with the Mann-Whitney U test, and a logistic regression model was developed to predict immune reconstitution. Among eight ISGs, the expression levels of IFI27 and IFI6 were significantly higher in INRs than IRs ( P =0.001 and 0.005, respectively). The model combining age, CD4 + T/CD8 + T ratio, IFI27, and IFI6 had the highest diagnostic value (AUC=0.836), with an optimal cut-off value of 0.6, sensitivity of 60.5%, and specificity of 98.1%. No significant change in the expression of IFI27 and IFI6 was observed in samples collected 3 years apart ( P =0.1232 and 0.4877, respectively), and the model score negatively correlated with ΔCD4 + T cells (r=−0.2888, P =0.0465). Enhanced expression of IFI27 and IFI6 in INRs are important characteristics that may serve as biomarkers of immune reconstitution after cART. The combination of age, CD4 + T/CD8 + T ratio, IFI27, and IFI6 was highly effective in discriminating INRs.